Glycine supplementation extends lifespan of male and female mice. Issue 3 (27th March 2019) - Miller, Richard A.; Harrison, David E.; Astle, C. Michael; Bogue, Molly A.; Brind, Joel; Fernandez, Elizabeth; Flurkey, Kevin; Javors, Martin; Ladiges, Warren; Leeuwenburgh, Christiaan; Macchiarini, Francesca; Nelson, James; et al.
Abstract: Diets low in methionine extend lifespan of rodents, though through unknown mechanisms. Glycine can mitigate methionine toxicity, and a small prior study has suggested that supplemental glycine could extend lifespan of Fischer 344 rats. We therefore evaluated the effects of an 8% glycine diet on lifespan and pathology of genetically heterogeneous mice in the context of the Interventions Testing Program. Elevated glycine led to a small (4%–6%) but statistically significant lifespan increase, as well as an increase in maximum lifespan, in both males ( p = 0.002) and females ( p < 0.001). Pooling across sex, glycine increased lifespan at each of the three independent sites, with significance at p = 0.01, 0.053, and 0.03, respectively. Glycine‐supplemented females were lighter than controls, but there was no effect on weight in males. End‐of‐life necropsies suggested that glycine‐treated mice were less likely than controls to die of pulmonary adenocarcinoma ( p = 0.03). Of the 40 varieties of incidental pathology evaluated in these mice, none were increased to a significant degree by the glycine‐supplemented diet. In parallel analyses of the same cohort, we found no benefits from TM5441 (an inhibitor of PAI‐1, the primary inhibitor of tissue and urokinase plasminogen activators), inulin (a source of soluble fiber), or aspirin at either of two doses. Our glycine results strengthen the idea that modulation of dietary amino acid levels can increase healthy lifespan in mice, and provide a foundation for further investigation of dietary effects on aging and late‐life diseases.